Mechanisms of Disturbed Rhythm, Etiology of Arrhythmias - Turayev Hikmatillo Negmatovich (Journal of Science in Medicine and Life, 2024)
Arrhythmias occur when the heart's regular rhythm changes, such as an abnormally fast or excessively slow heart rate. Cardiac arrhythmias are also detected when the heart beats irregularly, skips beats, or when separate parts - the atria and ventricles - contract out of sync. A normal heartbeat is controlled by electrical signals sent from a specific segment of heart muscle tissue called the sinus node. This natural pacemaker is located at the top of the right atrium. The heart is divided into four chambers: two atria above and two ventricles below. The atria's job is to fill the ventricles with blood, which then do the hard work of pumping it out to the rest of the body. During a normal heartbeat, an electrical impulse passes through muscle tissue, activating the ventricles a fraction of a second after the atria. In the case of arrhythmia, there are problems with this signal, the pulse deviates from the norm.